The Effect of Cash Ratio, Debt to Equity Ratio, Total Asset Turnover, Return on Asset and a Firm Size on Dividend Payout Ratio at Bank Persero Listed in IDX High Dividend 20 Period 2018-2021 - Virandani; Sofyan, Mohammad (Sinergi International Journal of Management and Business, 2023)
Several state-owned banks experienced drastic profit declines in 2000. However, these banks still provided a high percentage of dividends to their shareholders. This prompted the author's interest to analyze the effect of the cash ratio, debt to equity ratio, total asset turnover, return on assets and firm size on the dividend payout ratio of state-owned banks listed in IDX High Dividend 20 in the 2018-2021 period. This research is a quantitative research, with multiple linear regression data analysis techniques using the EViews 12 application as a data processing tool. The data used is secondary data, with the sample being the financial statements of state-owned banks listed in the IDX High Dividend 20 in the 2018-2021 period. The results of the study indicate that cash ratio, debt to equity ratio, total asset turnover, return on assets and firm size simultaneously have a significant effect on the dividend payout ratio of state-owned banks listed in IDX High Dividend 20 in the 2018-2021 period, with a significance level of 97.14%. Partially, however, cash ratio, debt to equity ratio, total asset turnover and return on assets have no significant effect on the dividend payout ratio, except for firm size which partially has a significant effect of 0.7143 on the dividend payout ratio of state-owned banks listed in IDX High Dividend 20 in the 2018-2021 period with a significance level of more than 95%. Prospective investors can use the size of a state-owned bank as a standard in determining the right state-owned bank to invest in, because the larger the size of the state-owned bank, the greater the percentage of dividends it distributes to its shareholders.